Causal relationship between immunophenotypes and mitral valve prolapse: a bidirectional Mendelian randomization study - Wang, Yue; Shen, Yusi; Tan, Lina; Hu, Liangbo; He, Min; Zeng, Xiaocong (Frontiers in Cardiovascular Medicine, 2024)
Emerging evidence indicates a significant link between various immune cell types and the development of heart valve disorders. Mitral valve prolapse (MVP) is a common condition that can lead to heart failure, arrhythmias, and even sudden death. Currently, the role of immune cells in MVP is not well understood. Thus, this study aimed to explore the causal relationship between immunophenotypes and the risk of MVP.This study conducted a two-sample Mendelian randomization (MR) analysis to examine the link between 731 immunophenotypes and MVP. Publicly available data from genome-wide association studies were used for both the exposures and outcomes.The primary method for assessing the causal relationship between mitral valve prolapse and the 731 immunophenotypes was the inverse variance weighted method.Additionally, to ensure the MR results were reliable and valid, sensitivity analyses, 2 including leave-one-out analysis, the Cochran Q test, and the Egger intercept test, were conducted.The findings indicated that multiple immune cell phenotypes potentially cause changes in the risk of developing MVP. After adjusting for the false discovery rate, nine immune phenotypes were found to increase the risk of MVP, while nine others appeared to decrease it. In addition, reverse MR analysis found no causal relationship between MVP and these eighteen immunophenotypes.Through genetic analyses, this research demonstrated a significant causal relationship between certain immune cells and MVP, providing new insights for future basic and clinical research.